Sufficientarianism - José Carlos R. Alcantud; Marco Mariotti; Roberto Veneziani (Queen Mary University of London, School of Economics and Finance, 2019)
Suflicientarianism is a prominent approach in political philosophy and in policy analyses. However, it is virtually absent from the formal normative economics literature. We analyse suflicientarianism axiomatically in the context of the allocation of opportunities (formalised as chances of success). We characterise the core suflicientarian criterion, which counts the number of agents who attain a "good enough" chance of success. The characterising axioms shed new light on the key ethical constituents of suflicientarianism: they express a liberal principle of non-interference, a form of minimal respect for equality, and a form of separability across individuals. Given the large indifference classes inbuilt in the core version, we also discuss two alternative social opportunity relations that refine the suflicientarian intuitions: the multi-threshold suflicientarian ordering and an incomplete relation focusing only on the suflicientarian strict preferences.
Keywords: D63; D70; 330; opportunities; chances of success; suflicientarianism